Pengaruh Tricokompos Dan Air Kelapa Terhadap Hasil Kubis Bunga (Brassica oleraceae var. botrytis L.) - Fadli, Mohamad; Syahrani, Syahrani; Septiani, Nina (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2015)
This research aims to find out the influence tricokompos and coconut water toward the result cauliflower research was conducted since May to August 2015, at agricultural landlongaparistreet maluhu village, Sub District Tenggarong, Kutai Kartanegara District, East Borneo Province.The research was arranged in a Randomized Complete Block Design (RCBD) with analysis of factorial 4x4 with deuteronomy three times. first factor treatment is giving tricokompos (T) that consists of 4 level, which consist of t0 (without fertilizer), t1(6 kg swath-1), t2(12kg swath-1), t3 (18 kg swath-1), and secondary factor treatment are a gift from coconut water (A) that consists of 4 level that is a0 (without hormone), a1 (0,125 L swath-1), a2 (0,250 L swath-1), and a3(0,375 L swath-1).The research results show that the treatment tricokompos do not affect to the six parameters and influential real highly visible to the three parameters, while coconut water does not have real an effect on to crops all parameters. The highest result per hectare of yield t3a3treatment at 18,48 t ha-1.